Buddhist Studies: The science of Buddhism - ถาวโร พระครูภาวนาวิริยานุโยค วิ. (Journal of Educational Review Faculty of Education in MCU, 2018)
There are 2 fields of knowledge or wisdom in the world: Buddhism and Science. Both are different but can be integrated. Knowledge in Buddhism occurs from many sources, such as 3 wisdoms, 8 Vijja and the Noble Eightfold Path. The opposite side of knowledge is ignorance. Ignorance is an arising cause in Paticcasamuppada. That is used in the worldly science as the process of all living beings. The ignorance is the falling cause is used in Buddhism. Both sciences are different but share similarity, that is, the knowledge in the worldly science creates scientific wisdom called research methodology consisting of 4 main principles; problems or suffering in Buddhism, causes of problems or the cause of suffering,